گرفتی په‌روه‌رده‌یی و میكانیزمی چاره‌سه‌ركردنی له‌ كوردستاندا - جەمال, هەوار; عومەر, تریفە (Sulaimani Journal for Humanities, 2018)
The reason behind the success most ofthe developed countriesin the world are their health and education dimensions. For instance: the magic of rising a country frommuddy and boggy ground Topractical model and creating modernindividuallike Singapore, was due to development and stabilizing education system, or the advance of a country such as Japan was from creating anintellectualindividual,this mighthave been done eitherthrough reformation or educating revolution that they reached the zenith of development. From this point of view, Kurdistan region after the 90s and establishing Kurdish government then offering a failed governmental experience for more than 25 years, is the result of obligatory and importance of conducting such a research, in a way that the result of the research demonstrates that the causes of these failuresare mainly theconsequence of disregarding the education sector. To escape this situation, following and at the same time implementing a suggested educating mechanism is a key factor to produce new individuals and the emergence of modern and advanced Kurdish society at the global level. In short, the importance of this research that accomplished through historical approach, descriptive analysis, and social survey is embodied inexecuting educational revolution that depended on a healthy educational philosophy in Kurdistan region.